The Effect of Taste and Service Quality on Customer Satisfaction at Padang Minang Sae Restaurant - Ahmad Kusworo (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
Food business is a business that is often desired by the community. The reason for choosing this food business is none other than because food is a basic human need. The first impression felt by customers when they first buy food or try a new food menu is definitely judged by the taste of the food. Taste for customers is the uniqueness of the taste of each food stall. Where to be able to judge the taste of a food can be seen from the aroma, taste, and level of maturity (Jones, 2000:109). This proves that the taste of culinary entrepreneurs will have a positive impact on customer satisfaction, besides that the quality of service is also very crucial to achieve satisfaction. The analysis method used in this study is a quantitative data analysis method using the multiple linear regression method. Multiple linear regression is a regression model that involves more than one independent variable. Multiple linear regression analysis is carried out to determine the direction and how much influence the independent variables have on the dependent variable Saleh & Utomo (2018). In this research example, multiple linear regression tests are carried out to get an idea of how the independent variables including taste and service affect the dependent variable, namely customer satisfaction. The analysis is carried out by processing data through SPSS. The results of this study indicate: First Hypothesis (H1), it can be concluded that Taste (X1) does not affect Customer Satisfaction (Y), Second Hypothesis (H2), it can be concluded that Service Quality (X2) does not affect Customer Satisfaction (Y), In the Third Hypothesis (H3), it can be concluded that simultaneously Taste (X1) and Service Quality (X2) do not affect Customer Satisfaction (Y).